2008
DOI: 10.2174/1874836800802010270
|View full text |Cite
|
Sign up to set email alerts
|

Displacement Ductility of Helically Confined HSC Beams

Abstract: This paper presents an experimental investigation of the effect of helix pitch and helix diameter on beam behaviour through testing 10 helically confined beams. Two groups of beams had exactly the same geometry and reinforcement; with the only differences being the helices diameter and pitch. 8 mm helix was used in the first group of beams and 12 mm bars in the second group. The helix pitches varied between 25 mm and 160 mm. Beams' cross section was 200 300 mm, with a length of 4 m subjected to four point load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The failure mechanism of the entire tested beams was yielding of tension steel bar and developing crack numbers and height followed by crushing the concrete in the top of compression zone. The extension of the crushing zone of group A was greater than that of the control beam B 1 and in increase with ρ ′ while the crushing zone of group B was smaller than that of the control beam and in decrease with f c ′ and that is clear in Figure (3).…”
Section: Table (5): Results Of the Tested Beams Cracking Load (P Cr )mentioning
confidence: 81%
See 3 more Smart Citations
“…The failure mechanism of the entire tested beams was yielding of tension steel bar and developing crack numbers and height followed by crushing the concrete in the top of compression zone. The extension of the crushing zone of group A was greater than that of the control beam B 1 and in increase with ρ ′ while the crushing zone of group B was smaller than that of the control beam and in decrease with f c ′ and that is clear in Figure (3).…”
Section: Table (5): Results Of the Tested Beams Cracking Load (P Cr )mentioning
confidence: 81%
“…Chloride free liquid admixture commercially named TopBond 603 complies with ASTM C 469-86 [12] was used. Properties and description of the used superplasticizar are shown in Table (3).…”
Section: Superplasticizer (Sp)mentioning
confidence: 99%
See 2 more Smart Citations
“…At present, many researches restrict the compression zone of beams in the form of spiral rebar or stirrups. Hadi and Elbasha [17] made experiments on 10 beams constrained by spiral rebar to study the ductility of beams with spiral rebar applied in the compression zone. Te results showed that the defection ductility coefcient of beams constrained by spiral rebar was larger, and the defection ductility coefcient increased as the pitch decreased.…”
Section: Introductionmentioning
confidence: 99%